2019
DOI: 10.15252/msb.20199071
|View full text |Cite
|
Sign up to set email alerts
|

Measuring glycolytic flux in single yeast cells with an orthogonal synthetic biosensor

Abstract: Metabolic heterogeneity between individual cells of a population harbors significant challenges for fundamental and applied research. Identifying metabolic heterogeneity and investigating its emergence require tools to zoom into metabolism of individual cells. While methods exist to measure metabolite levels in single cells, we lack capability to measure metabolic flux, i.e., the ultimate functional output of metabolic activity, on the single‐cell level. Here, combining promoter engineering, computational prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 83 publications
0
29
1
Order By: Relevance
“…It has been hypothesized that sensing of metabolic flux may depend on the accumulation of metabolites, which tightly correlate with pathway activity and trigger the appropriate cellular response ( 106 ). For example, the abundance of fructose-1,6-bisphosphate (FBP) tightly correlates with glycolytic flux in yeast and bacteria, and binding of FBP to a transcription factor allows for coupling of glycolytic flux to gene expression ( 107 , 108 ). Similarly, in pancreatic beta-cells, ATP correlates with glucose concentration and glycolytic activity and triggers insulin secretion by binding to ATP-sensitive K + -channels ( 109 ).…”
Section: Potential Mechanisms Of Nhe Regulation By Glucose Metabolismmentioning
confidence: 99%
“…It has been hypothesized that sensing of metabolic flux may depend on the accumulation of metabolites, which tightly correlate with pathway activity and trigger the appropriate cellular response ( 106 ). For example, the abundance of fructose-1,6-bisphosphate (FBP) tightly correlates with glycolytic flux in yeast and bacteria, and binding of FBP to a transcription factor allows for coupling of glycolytic flux to gene expression ( 107 , 108 ). Similarly, in pancreatic beta-cells, ATP correlates with glucose concentration and glycolytic activity and triggers insulin secretion by binding to ATP-sensitive K + -channels ( 109 ).…”
Section: Potential Mechanisms Of Nhe Regulation By Glucose Metabolismmentioning
confidence: 99%
“…3). 40,41 Having said this, for microbial production of PNPs to become a relevant supply chain of human therapeutics, efforts (i) to maximise activity of hard-to-express plant enzymes, (ii) relieve effects of toxic PNP intermediates, (iii) limit shunt product formation, (iv) stabilize titers/rates/yields of microbial PNP cell factories over prolonged cultivations, and (v) efficient down-stream processing, are all aspects needing further attention in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…A step beyond quantifying metabolite concentration is measuring flux, the relevant functional output of metabolic activity. Since fructose-1,6-bisphosphate (FBP) levels strictly correlate with glycolytic flux, a modified Bacillus subtilis CggR transcription factor that binds FBP, together with a synthetic promoter, were used to report on flux in budding yeast (Monteiro et al, 2019). Single-cell image analysis revealed that FBP concentration, and thus glycolytic flux, changes during the cell cycle, peaking around cytokinesis and in G1 phase.…”
Section: Llmentioning
confidence: 99%